MORPHOLOGICAL VARIABILITY OF PRUNUS MAACKII RUPR. IN NOVOSIBIRSK - V. S. Simagin; A. V. Lokteva (Труды по прикладной ботанике, генетике и селекции)
The morphological characters of flowers, fruits and leaves in the introduction population of Prunus maackii Rupr. have been studied in Novosibirsk. The range of variation in qualitative and quantitative traits as well as the average values of such quantitative traits and the level of their variation have been found out. These data may be used in defining the botanical diagnosis of the species. Besides, they may help to reliably identify the best genotypes.